Assessment of fatigue and recovery in elite cheerleaders prior to and during the ICU World Championships - Simon Gavanda; Christoph von Andrian-Werburg; Thimo Wiewelhove (Frontiers Media S.A., 2023)
IntroductionLittle is known about the demands of competitive cheerleading. Therefore, the objective of this study was to assess fatigue and recovery during preparation for world championships.MethodsFifteen participants from the German senior "All-Girl" and "Coed" national teams (nine males and six women) were recruited. Data were collected during the final preparation (T1 -T7) and competition days (C1 -C2). Heart rate variability (HRV) and resting heart rate (HR) were measured every morning. Data on training load, recovery, and stress (Short Scale for Recovery and Stress) were surveyed after training. Countermovement jump height (CMJ), sit-and-reach, and exercise-induced muscle damage (EMID) scores were taken in the afternoon.ResultsThere was a practically relevant decrease in CMJ (T2, T6). A trend for HR to increase (T5-C2) and HRV to decrease (T4, T6-C2) was evident. Through training, recovery decreased and recovered as C1 approached (mental performance: T2-T4 p = 0.004; T2-C1 p = 0.029; T3-T4 p = 0.029; emotional balance: T3-T4 p = 0.023; T3-C1 p = 0.014; general recovery status T1-T3 p = 0.008; T3-T4 p = 0.024; T3-C1 p = 0.041), whereas stress increased during the first days and returned to normal before C1 (emotional dysbalance: T2-T4 p = 0.014; T2-C1 p = 0.009; T3-T4 p = 0.023; T3-C1 p = 0.014). EMID scores increased for the upper and lower body between T3, T5-T7 (p ≤ 0.036) and T3, T6-T7 (p ≤ 0.047), respectively.DiscussionPre-competition training led to substantial fatigue, and most markers indicate that athletes do not compete fully recovered. This could possibly be avoided by optimizing the training load or implementing recovery strategies.